2001
DOI: 10.1006/viro.2001.1161
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Two Viruses with Large Genome Size Infecting Chrysochromulina ericina (Prymnesiophyceae) and Pyramimonas orientalis (Prasinophyceae)

Abstract: Two lytic viruses specific for Chrysochromulina ericina (Prymnesiophyceae) and for Pyramimonas orientalis (Prasinophyceae) were isolated from Norwegian coastal waters in June 1998. The lytic cycle was 14-19 h for both viruses; the burst size was estimated at 1800-4100 viruses per host cell for the Chrysochromulina virus and 800-1000 for the Pyramimonas virus. Thin sections of infected cells show that both viruses replicate in the cytoplasm and that they have a hexagonal cross section, indicating icosahedral sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
127
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 47 publications
4
127
0
Order By: Relevance
“…However, we found that prasinovirus-like phylotypes (and KBvp-8 in particular) dominated both the winter 2006 sample, which was prefiltered, and the summer samples, which were not. Some PCR bias does seem likely, as it has been reported that the AVS primers do not amplify the DNA polymerase gene of several representative members of genera within the family (Sandaa et al, 2001;Nagasaki et al, 2005). Different approaches, such as quantitative PCR assays targeting specific viral groups, will be needed to determine the actual in situ abundance of prasino-like viruses relative to other genera within the family Phycodnaviridae.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that prasinovirus-like phylotypes (and KBvp-8 in particular) dominated both the winter 2006 sample, which was prefiltered, and the summer samples, which were not. Some PCR bias does seem likely, as it has been reported that the AVS primers do not amplify the DNA polymerase gene of several representative members of genera within the family (Sandaa et al, 2001;Nagasaki et al, 2005). Different approaches, such as quantitative PCR assays targeting specific viral groups, will be needed to determine the actual in situ abundance of prasino-like viruses relative to other genera within the family Phycodnaviridae.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the presence of Mimivirus-like mutS gene in other giruses, we have undertaken a genomic sequencing survey of four giruses previously isolated from marine environments. The four giruses investigated are Pyramimonas orientalis virus (PoV-01B, 560-kb genome), Phaeocystis pouchetii virus (PpV-01B, 485-kb genome), Chrysochromulina ericina virus (CeV-01B, 510-kb genome) and Heterocapsa circularisquama virus (HcDNAV, 356-kb genome) (Jacobsen et al, 1996;Sandaa et al, 2001;Tarutani et al, 2001). The hosts of these viruses are phylogenetically distant and ecologically distinct unicellular marine algae.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore they play important roles in nutrient (Wilhelm and Suttle 1999) and biogeochemical (Fuhrmann 1999) cycling, and influence structure and diversity of microbial and phytoplankton communities (Fuhrmann 1999, Wommack andColwell 2000). Viruses have also been observed to infect a wide range of aquatic algae (Van Etten et al, 1991, Van Etten andMeints 1999), including bloom-forming marine phytoplankton (Nagasaki et al, 1994a, 1994b, Jacobsen et al, 1996, Nagasaki and Yamaguchi 1997, Sandaa et al, 2001.…”
Section: Introductionmentioning
confidence: 99%